Thermodynamic and kinetic studies on CO2 capture with PolyVBTMAArg - Raja Shahrom, M.S. (Elsevier Ltd, 2018)
This paper discusses the technologies for capturing CO2 from the natural gas using polyVBTMAArg, a type of poly(ionic liquids) with an amino acid as the anion. The results revealed that the CO2 uptake increased from 3.23 mmol/g to 7.91 mmol/g at 1â10 bar, 298 K due to both chemical absorption and physical adsorption increments. Four adsorption isotherm models were applied to study the interaction between adsorbate and adsorbent to study the physical adsorption i.e. Freundlich, Langmuir, Dubinin Raduschkevich and Temkin isotherms at 298 K, 313 K and 333 K. Promising results were obtained that suggested the Freundlich model and the pseudo-first order model are well fitted with the kinetic data at 298 K with a 0.9943 R2 value. This study has provided empirical evidence to the current body of knowledge pertaining to CO2 capture technologies. Â© 2018 Elsevier Ltd